(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
In the article were investigated, issues and organizational and legal framework for conducting fiscal policy in municipal bonds and local debt. W ere proved that the negative trends in terms of formation of local budgets increased risk of default, which in turn leads to the formation of the debt crisis. The main disadvantages arrangement of municipal bonds is their low investment attractiveness, social and economic instability and political situation, lack of regional stock markets and the lack of guarantees of local governments to repay municipal debt. The author determined that the optimal focus using borrowed funds are investing in infrastructure that will increase revenues to the local budget